Community-based model for rabies control in Bali: An EcoHealth Approach - Jatikusumah, A.; Darmawan, R.D.; Widyastuti, M.D.W.; Sunandar; Basuno, E.; Putra, A.A.G.; Willyanto, I.; Estoepangestie, S.; Gilbert, Jeffrey (2013)
In 2008, Bali was struck by rabies and since then rabies had spread to 273 of 723 villages in Bali and the number of human fatalities had reached 145. The concerted effort of government and stakeholders to combat this disease is progressing well. At present, the government’s control program consists of mass vaccination, selected targeted culling, and education with a goal to eradicate rabies from the island by 2015. The additional effort on the establishment of participatory rabies prevention, control and surveillance system within the local community level is needed to improve the ongoing and future rabies control efforts. As part of a project “Ecohealth Approaches for Optimizing the Rabies Control Program in Bali”, organized by CIVAS, with support from the IDRC and led by ILRI, within the project, we developed and piloted a community-based model for sustainable rabies control driven by community involvement in two villages in Karangasem and Gianyar districts in Bali. Promising results from pilot villages model indicates high participation of the community (formed 82 cadres in Gianyar and Karangasem) on the public awareness, early reporting, early response and early detection on bitten cases and supporting on government program particularly on the mass vaccination by registration data of the dog within community to achieved high coverage on vaccination (>70%). This efforts suggests that involving community members more actively in villages through the institutionalization of ‘rabies village working groups’ could substantially improve surveillance activities with possible effects on improving dog management and vaccination coverage. With little direct financial input such participation creates a sense of community ownership. This approach showed affective on improving early response, early detection and surveillance system that could be used effectively across other districts in Bali. The continued fight against rabies on Bali and elsewhere in the developing world would benefit significantly from engaging communities more actively in control and surveillance efforts.